A Hygiene And Sanitation Assessment Of Warmindo Food Establishments In The Banyuraden Area - Wahyu Joko Triono, Muhammad; Haryono, Haryono; Narto; Sri Muryani (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Food is one of the factors that can affect human health. Food that is suitable for consumption is food that is of good quality, does not contain poison and is still fresh. Therefore, existing restaurants must implement sanitary hygiene in accordance with Permenkes No. 2 of 2023 concerning Implementation Regulations of Government Regulation No. 66 of 2014 concerning Environmental Health. In Warmindo restaurants in the Banyuraden area, there are still restaurants with incomplete facilities and unhygienic behavior of food handlers such as smoking while processing food and taking ice by hand, which can adversely affect food or even cause food poisoning.